Analysis of the Differences between the Cambridge Curriculum and the Merdeka Curriculum at Islamic Primary School - Nurus Shobach Izakiyah; Nadlir Nadlir (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of writing this article is to understand the different components of the Cambridge Curriculum and the Merdeka Learning Curriculum at Islamic Primary School so that it can make it easier for madrasas to be able to choose a curriculum that suits the needs of the Islamic Primary School. This research is qualitative research using a library study type of research. This research uses data collection techniques in the form of articles, books and notes from previous research results in both the Cambridge Curriculum and the Merdeka Belajar Curriculum. The data analysis technique in the research is analyzing the components, advantages and disadvantages of implementing the Cambridge Curriculum and the Merdeka Learning Curriculum in Islamic Primary School. The results of the research obtained by researchers are that the Merdeka Learning Curriculum and the Cambridge Curriculum have 12 (twelve) components, namely constituents, general & specific objectives, targets, learning approaches, focus, learning structure, teachers, students, emphasis, assessment, curriculum structure, language introduction, costs and recognition of the curriculum. The Cambridge Curriculum and the Merdeka Belajar Curriculum have their respective advantages and disadvantages. Therefore, a Islamic Primary School needs to consider the madrasah's vision & mission, student needs, existing resources and support from parents in selecting a curriculum that suits the Islamic Primary School's needs. The Cambridge Curriculum and the Merdeka Belajar Curriculum can be applied simultaneously at Islamic Primary School. The success of a curriculum is influenced by collaboration between teachers, parents and students.